2017
DOI: 10.1111/acer.13363
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Prenatal Alcohol Exposure is Related to Smaller Corpus Callosum in Newborn MRI Scans

Abstract: Background MRI studies have consistently demonstrated disproportionately smaller corpus callosa in individuals with a history of prenatal alcohol exposure but have not previously examined the feasibility of detecting this effect in infants. Tissue segmentation of the newborn brain is challenging because analysis techniques developed for the adult brain are not directly transferable, and segmentation for cerebral morphometry is difficult in neonates, due to the latter’s incomplete myelination. This study is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 62 publications
5
65
0
Order By: Relevance
“…The findings of lower total GM volume are consistent with results on older children, which suggests that they are pervasive (Archibald et al, 2001;Nardelli, Lebel, Rasmussen, Andrew, & Beaulieu, 2011). Structurally, PAE has also been linked to decreased corpus callosum area (Jacobson et al, 2017). Diffusion tensor imaging (DTI) studies on the topic have found lowered axial diffusivity (AD) values in PAE infants (Donald, Roos, et al, 2015;Taylor et al, 2015).…”
Section: Alcohol As a Prenatal Exposuresupporting
confidence: 76%
See 1 more Smart Citation
“…The findings of lower total GM volume are consistent with results on older children, which suggests that they are pervasive (Archibald et al, 2001;Nardelli, Lebel, Rasmussen, Andrew, & Beaulieu, 2011). Structurally, PAE has also been linked to decreased corpus callosum area (Jacobson et al, 2017). Diffusion tensor imaging (DTI) studies on the topic have found lowered axial diffusivity (AD) values in PAE infants (Donald, Roos, et al, 2015;Taylor et al, 2015).…”
Section: Alcohol As a Prenatal Exposuresupporting
confidence: 76%
“…A 2016 study by found that PAE was associated with reduced overall GM volumes, most notably in bilateral amygdalae, left hippocampus, and left thalamus at 3 weeks of age and with slightly delayed socio-emotional development compared with control infants at 6 months of age. Structurally, PAE has also been linked to decreased corpus callosum area (Jacobson et al, 2017). Structurally, PAE has also been linked to decreased corpus callosum area (Jacobson et al, 2017).…”
Section: Alcohol As a Prenatal Exposurementioning
confidence: 99%
“…Some structures may be disproportionately affected in FASD with larger proportional reductions in specific deep gray matter structures such as the caudate and putamen (Nardelli, Lebel, Rasmussen, Andrew, & Beaulieu, 2011;Roussotte et al, 2012). These brain volume reductions have also been reported in infants and neonates with PAE for the corpus callosum (Jacobson et al, 2017) and gray matter (Donald et al, 2016). In addition, larger volume reductions have been observed in males with FASD suggesting sex differences (Chen, Coles, Lynch, & Hu, 2012;Dudek, Skocic, Sheard, & Rovet, 2014;Treit et al, 2017).…”
Section: Introductionmentioning
confidence: 77%
“…Significantly, the corpus callosum, a major white matter structure essential for interhemispheric communication, has been reported to be disproportionately smaller in alcoholexposed neonates (195,199,200,(204)(205)(206). Structural deficits in the corpus callosum may lead to poor cognitive performance, and impaired sensory, motor and higher-order neural communication (204)(205)(206), as a result of poor connectivity, dysregulated interhemispheric integration, and impaired processing. Likewise, diffusion imaging studies link abnormal callosal microstructure and structural coherence with impaired myelination, diffuse fiber bundles and poor axonal integrity (204,207).…”
Section: Clinical Presentation Of Paementioning
confidence: 99%
“…Structural deficits in the corpus callosum may lead to poor cognitive performance, and impaired sensory, motor and higher-order neural communication (204)(205)(206), as a result of poor connectivity, dysregulated interhemispheric integration, and impaired processing. Likewise, diffusion imaging studies link abnormal callosal microstructure and structural coherence with impaired myelination, diffuse fiber bundles and poor axonal integrity (204,207). Significantly, these neuroimaging studies corroborate the first autopsy studies of FAS, including those revealing impaired cell migration, and agenesis or thinning of the corpus callosum (183,208).…”
Section: Clinical Presentation Of Paementioning
confidence: 99%